Foreign Direct Investment in New Member State of the EU and Western Balkans : Taking Stock and Assessing Prospects - Jirasavetakul, La-Bhus Fah (IMF Working Papers; Working Paper ;, 2018)
FDI has played a strong role in the export-led growth of eastern European countries that are now members of the European Union (EU). Largely sourced from advanced Europe, FDI inflows were motivated by the intention to pursue new markets and cost efficiency. Over time, foreign investment has restructured the exports sector in these countries in favor of products that are considered more technology-intensive. As these countries face skills shortage and rising wages, what is needed for FDI to continue playing a strong role? Can the Western Balkan countries, who are not yet EU members and have in recent years stepped up financial incentives and policy initiatives to court investors, emulate the experience? This paper takes stock of the FDI experience of both these groups and tries to estimate their potential gains from additional policy efforts.